Answer:
Step-by-step explanation:
To do pythagoras theorem
You apply the rules
Which state that,in right angled triangle the square of hypotenus is equal to sum of the square of the other two side. That is
hyp^2=opp^2+adj^2
Answer:
If you are looking for the slope-intercept equation, it's y=−3x−1. Hope you have a great rest of the day and stay safe, be kind, and go beyond Plus Ultra!
[ - 6 * x^2 * y^8 + 12* x * y^3 - 36 * x * y^2 ] / [6*x*y^2] =
[-6x^2 y^8 ] / [6xy^2] + [12x y^3] / [6xy^2] - [36xy^2] / [6xy^2] =
- xy^6 + 2y - 6
Answer: - xy^6 + 2y - 6